2013
DOI: 10.1007/s00248-013-0321-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Signaling Ecology and Potential Applications During Aquatic Biofilm Construction

Abstract: In their natural environment, bacteria and other microorganisms typically grow as surface-adherent biofilm communities. Cell signal processes, including quorum signaling, are now recognized as being intimately involved in the development and function of biofilms. In contrast to their planktonic (unattached) counterparts, bacteria within biofilms are notoriously resistant to many traditional antimicrobial agents and so represent a major challenge in industry and medicine. Although biofilms impact many human act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…Since QS has been reported to occur under flow conditions in Nature 19 28 , we asked how our findings in engineered E . coli compare to the natural system in P .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Since QS has been reported to occur under flow conditions in Nature 19 28 , we asked how our findings in engineered E . coli compare to the natural system in P .…”
Section: Resultsmentioning
confidence: 96%
“…In nature, biofilms are prevalent in rivers, streams, intertidal regions, sinking marine particles and groundwater flow 16 17 18 . In clinical settings, biofilms form on flow-exposed catheters and implants 19 . Biofilms in the human body can experience a multitude of fluid flow regimes ranging from interstitial flow in lymphatic microvessels 20 to laminar flow in the intestine 21 , the microvasculature 22 , and the urinary tract 23 .…”
mentioning
confidence: 99%
“…Subsequent studies have shown quorum-signalling inhibition to be present in other plants (Gao et al , 2003) and marine invertebrates (Manefield et al , 2000), as well as other micro-organisms (Golberg et al , 2013). Mechanisms involved in quorum-signalling inhibition [reviewed by Vega et al (2014)] include the production of quorum-signalling-inhibiting compounds such as furanones (de Nys et al , 2006) produced by D. pulchra and enzymic degradation (quorum quenching) of the signal (Wang & Leadbetter, 2005). In a recent study, we observed that Escherichia coli enhanced its survival by producing indole during growth as a mixed culture with Pseudomonas aeruginosa (Chu et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first formation process of biofilm is the adhesion of free bacteria to biological or non‐biological surfaces. Once firmly attached, the bacteria promptly gather together, which was often mediated by quorum sensing, two‐component systems or c‐di‐GMP‐mediated regulation (Vega et al ., 2014). The fixed bacteria then secrete extracellular polysaccharides to form a mixed extracellular matrix with open water channels.…”
Section: Introductionmentioning
confidence: 99%